2015
DOI: 10.1371/journal.pone.0145382
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Psychosocial Resilience and Physical Health Status of Western Australian Urban Aboriginal Youth

Abstract: BackgroundPsychosocial processes are implicated as mediators of racial/ethnic health disparities via dysregulation of physiological responses to stress. Our aim was to investigate the extent to which factors previously documented as buffering the impact of high-risk family environments on Aboriginal youths’ psychosocial functioning were similarly beneficial for their physical health status.Method and ResultsWe examined the relationship between psychosocial resilience and physical health of urban Aboriginal you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 66 publications
0
23
0
1
Order By: Relevance
“…Pearson correlation coefficients for continuous data or independent t‐tests with dichotomous variables were calculated with related constructs. For hypothesis testing, studies were identified with significant correlations between resilience and psychological complaints, smoking, engagement, recreation and diet . Therefore hypothesis testing was performed with five related constructs: Workers have significant higher scores on the BRS when they: (a) Do not smoke, (b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson correlation coefficients for continuous data or independent t‐tests with dichotomous variables were calculated with related constructs. For hypothesis testing, studies were identified with significant correlations between resilience and psychological complaints, smoking, engagement, recreation and diet . Therefore hypothesis testing was performed with five related constructs: Workers have significant higher scores on the BRS when they: (a) Do not smoke, (b).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, significant positive correlations were identified between resilience and work engagement . Negative correlations were identified between resilience and psychological complaints . Additionally, resilience is related to many life style factors including, smoking, recreation and diet …”
Section: Introductionmentioning
confidence: 97%
“…Perhaps the most striking variation between these groups was that physical issues including doing usual daily activities and dealing with fatigue were the top priorities for Non-Indigenous people, while money worries, dealing with sadness and keeping a strong spirit appeared to be more frequently reported by Indigenous people. Possible explanations may be that Indigenous people historically have been more exposed to adversity and trauma and therefore may have more resilience and less perceived unmet needs (Hopkins, Shepherd, Taylor, & Zubrick, 2015) or alternatively that Indigenous people have poorer access to services (Condon, Barnes, Armstrong, Selva-Nayagam, & Elwood, 2005) and because of this and/or other cultural factors have lower expectations of support provision when it comes to physical/daily living and psychological issues. e One Non-Indigenous participant with missing information in this item; f Two Non-Indigenous participants with missing information in this item; g Three Non-Indigenous participants with missing information in this item; h Four Non-Indigenous participants with missing information in this item.…”
Section: This Study Compares the Perceived Unmet Needs Of Indigenous Andmentioning
confidence: 99%
“…4 Despite these limitations, a brief or rapid review involving one relevant database over a recent five year period provides useful information on the quantity of research produced in a given setting which was the aim of the review by Eades et al 4 Moreover, one evaluation of four rapid reviews found that their findings, while not as extensive, did not differ greatly from four completed systematic reviews on the same topics. 101 Cross-sectional design Yes a Gardner et al 2015 102 Cross-sectional design No Lalla et al 2015 103 Cross-sectional design Yes Radford et al 2015 104 Cross-sectional design Yes Hopkins et al 2015 105 Cross-sectional design No Arjunan et al 2015 106 Cross-sectional design No Katzenellenbogen et al 2015 107 Cross-sectional design No Pearce et al 2015 108 Cross-sectional design No Spurling et al 2014 109 Cross-sectional design Yes a Scott et al 2014 110 Cross-sectional design No Timms et al 2014 111 Cross-sectional design No Chung et al 2014 112 Cross-sectional design Yes Askew et al 2013 113 Cross-sectional design Yes a Lopez et al 2014 114 Cross 141 Qualitative Yes 153 Mixed methods Yes Gould et al 2015 154 Mixed methods No Jersky et al 2015 155 Mixed methods No Dennis et al 2015 156 Mixed methods No Govil et al 2014 157 Mixed methods Yes Thomas et al 2013 158 Mixed methods No Canuto et al 2013 159 Mixed methods No Homer et al 2012 160 Mixed methods No Larkins et al 2011 161 Mixed methods No Harris et al 2014 162 Cohort study No McDonald et al 2014 163 Cohort study No Jamieson et al 2013 164 Cohort study No Knight et al 2013 165 Cohort study No Webster et al 2013 166 Cohort study No Davis et al 2012 167 Cohort study No Robinson et al 2012 …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%
“…Biddle recommends taking the most efficient approach possible to data collection and analysis in order to minimise participant burden. 180 In summary, research data published in the last five years and indexed on PubMed, 107 Aboriginal health liaison 8,041 b No O'Connor et al 115 Chlamydia 7,103 b Yes Dutton et al 170 Health 128 Albuminuria 860 No Lopez et al 114 Ischaemic heart disease 833 b Yes Hopkins et al 105 Psychological resilience 677 No Arjunan et al 106 Tobacco use 663 No Jamieson et al 164 Oral 113 Stressful events in children 344 b No Lalla et al 103 Oral mucosal disease 342 No Radford et al 104 Dementia 336 No Whish-Wilson et al 99 Birth outcomes 301 Yes Roberts-Thomson et al 117 Oral health 251 No Dorrington et al 174 Pap smears 213 No Gardener et al 102 Children 205 No Wong et al 126 Midwifery 177 Infant health 175 Yes Luke et al 181 Suicidal 169 Breast feeding 159 Yes Webster et al (Gudaga study) 166 Child growth 157 No Scott et al 110 Sexual health 155 No Miller et al (Gudaga study) 118 Child language assessment 150 No Arrow 100 Oral …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%